STEM Laboratory for Schools in Gandaki Province and Beyond - Adhikari, Santosh; Bhandari, Dhaka Ram; Bist, Sandeep; Lamichhane, Aadarsha (Journal of Engineering and Sciences, 2022)
Abstract available with the full text.